Not by Productivity Alone: How Visibility and Specialization Contribute to Academic Earnings - Leahey, Erin (American Sociological Review, 2007)
The popular adage “publish or perish” has long defined individual career strategies as well as scholarly investigations of earnings inequality in academe, as researchers have relied heavily on research productivity to explain earnings inequality among faculty members. Academia, however, has changed dramatically in the last few decades: it has become larger and more demographically diverse, and fears of overspecialization prompt calls for interdisciplinary approaches. In this new environment, other factors, in addition to productivity, are likely relevant to our understanding of earnings differentials. In this article, I assess whether two additional factors—visibility and the extent of research specialization—contribute to men's earning advantage. Using probability samples of tenure-track academics in two disciplines, a variety of data sources, and innovative measures, I find that both factors are highly relevant to the process by which earnings are determined. Women earn less than men largely because they specialize less. Lower levels of specialization hinder productivity, productivity enhances visibility, and visibility has a direct, positive, and significant effect on salary. I discuss the practical implications of these findings and lay the foundation for a broader theory of the role of research specialization in work processes.